2019
DOI: 10.1002/celc.201900577
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Nanocarbon Can Simultaneously Work as Platform and Signal Generator for Label‐Free Immunosensing

Abstract: Electroactive nanocarbon can be defined as a carbon nanomaterial that contains electrochemically reducible oxygen functionalities. We show here how an electroactive nanocarbon material can work both as a platform and as a signal generator when developing an immunosensor for the detection of mycotoxins. The suitability of the material for the immobilization of the biorecognition element by the formation of multiple noncovalent interactions, and the concurrent ability to provide a significant reduction peak are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The large surface area of the graphene sheets and the fast heterogeneous charge transfer on the material has been exploited for the immobilization and detection of electroactive molecules, whit the graphene label having a role in the enhancement of the electrochemical signal. Finally, latest studies have shown how nano‐graphene oxide was used as the platform and the label at the same time, with the signal arising from the electrochemical reduction of the oxygen containing groups on the graphene platform, without the need of adding the label in the last step …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large surface area of the graphene sheets and the fast heterogeneous charge transfer on the material has been exploited for the immobilization and detection of electroactive molecules, whit the graphene label having a role in the enhancement of the electrochemical signal. Finally, latest studies have shown how nano‐graphene oxide was used as the platform and the label at the same time, with the signal arising from the electrochemical reduction of the oxygen containing groups on the graphene platform, without the need of adding the label in the last step …”
Section: Discussionmentioning
confidence: 99%
“…In order to understand whether the same approach could work also with bulkier receptors, a similar study was carried out by using an antibody as the biorecognition element for the detection of the same analyte . In contrast with the previous results, a further decrease in the GONC reduction signal was observed upon the analyte incubation, rather than a signal restoration.…”
Section: Graphene Used As Platform and Labelmentioning
confidence: 98%
“…Overall, CNPs have incredible features such as high porosity, good conductivity, high surface area and electrocatalytic activity, which make them ideal for Ab immobilization, ET enhancement and Ab 2 labeling [64]. Moreover, the use of GO nanocolloids (GONCs), both as immobilization platforms and electroactive tracers, proved to be of great interest in this context [65].…”
Section: Carbon-based Nanomaterials (Nms)mentioning
confidence: 99%
“…25 In addition to that, a significant cathodic peak is obtained from the electrochemically reducible OCGs that are present on the material surface. 26,27 Among the OCGs on graphene surface, those that can undergo further electrochemical reduction at potentials between −0.9 and −1.5 V in neutral buffers are epoxy, aldehyde, and peroxy groups, while the reduction of carbonyl, carboxyl, and ester groups requires harsher conditions, acidic media, and higher potentials above −2.0 V. 28 While the intrinsic electroactivity of graphene oxide materials is well-known in the scientific community, only a few studies have exploited this property using nanographene oxides as labels for analytical applications. 26,27,29 In the approach we propose here, a nanographene oxide material will be conjugated to the DNA primers through the formation of a covalent bond.…”
Section: ■ Introductionmentioning
confidence: 99%
“…26,27 Among the OCGs on graphene surface, those that can undergo further electrochemical reduction at potentials between −0.9 and −1.5 V in neutral buffers are epoxy, aldehyde, and peroxy groups, while the reduction of carbonyl, carboxyl, and ester groups requires harsher conditions, acidic media, and higher potentials above −2.0 V. 28 While the intrinsic electroactivity of graphene oxide materials is well-known in the scientific community, only a few studies have exploited this property using nanographene oxides as labels for analytical applications. 26,27,29 In the approach we propose here, a nanographene oxide material will be conjugated to the DNA primers through the formation of a covalent bond. After which, the resulting conjugate will be employed for the amplification of the Cauliflower Mosaic Virus (CaMV) 35S promoter sequence, one of the most commonly used genetic markers for the detection of genetically modified organisms (GMOs).…”
Section: ■ Introductionmentioning
confidence: 99%